Attitudes of English language teachers toward the implementation of school-based assessment in ESL classrooms, in Serian district / Helda Jugah - Jugah, Helen (2015)
This study was on the attitudes of English Language teachers in Serian District, toward the implementation of SBA in their English Language classroom. The objectives of this study were to investigate the extent of 53 English Language teachers' knowledge of the content of School-Based Assessment (SBA) document, their attitudes toward School-Based Assessment and their attitudes toward the implementation of SBA in English Language classrooms. It also investigated the relationship between teachers' attitudes in implementing SBA in their English Language classes with teachers' teaching experience, teachers' choice of assessment, teachers' level of knowledge and teachers' attitudes toward SBA. In addition, this study also identified other factors that influence English Language teachers' attitudes toward the implementation of SBA in their English Language classroom. The method used for this study was a questionnaire. The data were analysed using SPSS 16 and categorized accordingly. The findings showed that teachers needed professional development on SBA. They had mixed feeling about SBA and the implementation of SBA in their English Language classroom. Factors like time constraint, classroom size, Internet access, extreme different levels of students in the class and no proper modules and guidelines did influence teachers' attitudes in implementing SBA in their classroom. No proper training given to teachers is also one of the factors that influence teachers' attitudes toward the implementation of SBA in their English Language classroom